2021
DOI: 10.1111/jse.12809
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin of species diversity on the Qinghai–Tibet Plateau

Abstract: The Qinghai–Tibet Plateau (QTP) sensu lato (sl) houses an exceptional species diversity in Asia. To develop a comprehensive understanding of species diversity in this fascinating region, we reviewed recent progress from biogeographic, paleogeographic, paleontological and genomic research of both plants and animals in the QTPsl. Numerous studies have been conducted to examine whether the QTPsl uplift triggered the production of rich species diversity there, whether a Quaternary “unified ice sheet” eliminated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 170 publications
(251 reference statements)
3
61
0
Order By: Relevance
“…Furthermore, Betaproteobacteria, one of the most important groups of Proteobacteria, had a significant abundance advantage in U. longissima, which has been reported to be able to adapt lichens to nutritionally poor environments (Wedin et al, 2016). Indeed, almost all the U. longissima in this study grow at high altitudes, where the environment is relatively extreme and harsh (Mao et al, 2021). Therefore, Betaproteobacteria may play an important role in adapting to the extreme condition in Tibet.…”
Section: A B C Dmentioning
confidence: 61%
“…Furthermore, Betaproteobacteria, one of the most important groups of Proteobacteria, had a significant abundance advantage in U. longissima, which has been reported to be able to adapt lichens to nutritionally poor environments (Wedin et al, 2016). Indeed, almost all the U. longissima in this study grow at high altitudes, where the environment is relatively extreme and harsh (Mao et al, 2021). Therefore, Betaproteobacteria may play an important role in adapting to the extreme condition in Tibet.…”
Section: A B C Dmentioning
confidence: 61%
“…Range shifts driven by Quaternary climatic oscillations in these regions (Liu et al, 2012; Mao et al, 2021) may have led to secondary contact, hybridization and plastome introgression. For example, as found in many species (Liu et al, 2012), the two lineages in the Hengduan Mountains maintained relatively stable population sizes across the Quaternary (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, as found in many species (Liu et al, 2012), the two lineages in the Hengduan Mountains maintained relatively stable population sizes across the Quaternary (Figure 3). In contrast, both the PP and NC lineages showed a large‐scale decline in population sizes, probably in response to considerable temperature decreases and glacial development in northern China and the platform region during the Quaternary glacial periods when climate deteriorated greatly (Liu et al, 2012; Mao et al, 2021), but they recolonized regions from where they had retreated when the climate became warmer, leading to range expansion at the end of the glacial periods. During glacial retreat in the Hengduan Mountains, both the PP and NC lineages hybridized with the SH and NH lineages, resulting in plastome introgression between them and genetic admixtures in populations in the contact regions.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, transcriptome sequencing has been described as a powerful method for genome-wide analysis of high-altitude adaptation and is cheaper and easier available than the nuclear genome. Additionally, QTP is the highest plateau in the world, with an extreme environment of hypoxia, low temperature, and strong solar radiation (Mao et al, 2021). Solar radiation is one of the main stresses faced by alpine plants, and chloroplasts, as the site for photosynthesis, may have acquired adaptive strategies to strong solar radiation (Yoshida et al, 2019).…”
Section: Adaptive Evolutionmentioning
confidence: 99%
“…Alpine species on the QTP have to evolve to have a high ability to adapt to extremely harsh environments (Thompson et al, 2000;Norsang et al, 2011). Intense UV radiation is a major environmental stressors for plants, and recent studies have revealed candidate genes for plateau adaptability, mainly associated with UV radiation in a variety of plants (Mao et al, 2021). We anticipated that some genes in the chloroplast genome of I. hypsophila might have undergone adaptive evolution to adapt to the alpine environment, although overall genome size, structure, and gene number have changed slightly.…”
Section: Adaptive Evolutionmentioning
confidence: 99%